Analisis Penerimaan Layanan Mobile Banking dengan Integrasi Task Technology Fit (TTF) dan Unified Theory of Acceptance and Use of Technology (UTAUT) - Yudistira, Miranty; Zaenal Abidin, Dodo (Jurnal Manajemen Sistem Informasi, 2024)
Mobile Banking improvement is not really good, number of Internet users via cellular phones (mobile phones) is not proportional to the increase in users of digital banking services, especially mobile banking. The development of Mobile Banking, especially for Bank Syariah Indonesia (BSI) customers, shows that data is not balanced between User Registration and User Activation. The purpose of this study was to determine the factors that affect the acceptance of mobile banking user adoption using integrated Task technology Fit (TTF)-Unified Theory of Acceptance and Use of Technology (UTAUT). TTF-UTAUT Model uses eight variables, namely task characteristics, technology characteristics, task technology fit, performance expectancy, effort Expectancy, social influence, facilitating condition and user adoption. This study began by distributing questionnaires through google form to 400 respondents Then the questionnaire data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM), SmartPLS tools. Based on the analysis, the TTF-UTAUT model was able to explain the acceptance of mobile banking usage by 77.3%. Factors that have a significant influence on the acceptance of mobile banking usage Services include: task technology fit to user adoption; performance expectancy to user adoption; effort expectancy to user adoption; effort expectancy to performance expectancy; social influence to user adoption; facilitating condition to user adoption; task characteristics to effort expectancy and task technology fit to performance expectancy. To increase the acceptance of mabile banking services, socialization, innovation and simulation of services on the application are needed.